"New Normality" of Economics, Politics and society in the conditions of COVID-19 and After - A. N. Kuriukin (Модернизация, инновация, развитие, 2021)
Purpose: to try to delineate the boundaries and formulate the characteristic features and signs of a "new normalcy", which, already taking shape today in the course of the ongoing development of the coronavirus pandemic, will in the long term be a determining factor for the further economic, political and social development of modern civilization.Methods: consists in a complex research paradigm, which includes the principles of systemic, theoretical-cognitive, institutional, instrumental and interdisciplinary approaches, mediated by the accepted in social science ideas about the relationship and interaction of subjective and objective factors in social processes with relative independence of the subject.Results: the general direction of the development of civilization will be the preservation, in the foreseeable future, of the requirements of social distancing and restrictions on cross-border mobility. Remote forms of work, low-contact manufacturing and the formation of Industry 4.0 will come to the fore in the economy. In society, there will be a need to revise modern social values, in the direction of the transition from the degree of satisfaction of individual and personal needs to the availability of such satisfaction as the main value. The central issue of post-image politics will be the question of whether the pandemic will bring about an anti-democratic rollback and an evolving authoritarianization of power, or, on the contrary, will become an impetus for the positive development of democracy, an increase in the role of civil society and the political participation of citizens.Conclusions and Relevance: with regard to the economy, society and politics, it is stated that, on the one hand, they will experience unprecedented transformational pressures under the influence of the ongoing pandemic crisis, but at the same time, they will face a choice – to maintain crisis stagnation hoping to “just survive” or perceive the crisis as source of new opportunities for development and progress.